2013
DOI: 10.1177/0192623313503516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lersivirine on Canine and Rodent Thyroid Function

Abstract: Lersivirine is a nonnucleoside reverse transcriptase inhibitor (NNRTI) being developed for the treatment of HIV-1 infection. Like other NNRTIs, lersivirine is a potent enzyme inducer in rodents capable of inducing a number of hepatic enzymes including those involved in its own metabolism. Preclinically lersivirine has been associated with hepatocellular hypertrophy and thyroid gland follicular cell hypertrophy in rats, mice, and dogs. In rodents, we show that development of thyroid hypertrophy is related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Hepatocellular neoplasms, altered foci, and centrilobular hypertrophy in rats given lersivirine were attributed to hepatic microsomal enzyme 358 NAMBIAR ET AL. TOXICOLOGIC PATHOLOGY induction that has been previously reported for lersivirine (Figure 2C; Houle et al 2013;Walker et al 2009). These microscopic findings often manifested as macroscopic findings such as enlarged liver and/or hepatic masses.…”
Section: Macroscopic and Microscopic Findings Liversupporting
confidence: 75%
See 3 more Smart Citations
“…Hepatocellular neoplasms, altered foci, and centrilobular hypertrophy in rats given lersivirine were attributed to hepatic microsomal enzyme 358 NAMBIAR ET AL. TOXICOLOGIC PATHOLOGY induction that has been previously reported for lersivirine (Figure 2C; Houle et al 2013;Walker et al 2009). These microscopic findings often manifested as macroscopic findings such as enlarged liver and/or hepatic masses.…”
Section: Macroscopic and Microscopic Findings Liversupporting
confidence: 75%
“…Short-term and chronic nonclinical studies with lersivirine have demonstrated liver and thyroid effects consistent with hepatic enzyme induction. Evidence of hepatic enzyme induction in rats included increased liver weights; hepatocellular hypertrophy; increased hepatocellular smooth endoplasmic reticulum; increased hepatic CYP 3A1, 2B1, and 2B2; increased hepatic uridine diphosphate glucuronosyl transferase (UDP-GT); and thyroid hypertrophy/ hyperplasia (Houle et al 2013;Walker et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light microscopic changes were observed in the liver (hepatocellular hypertrophy), pituitary (hypertrophy of basophils of the pars distalis), and the thyroid gland (decreased colloid and hypertrophy of follicular epithelium); these microscopic changes were attributed to an adaptive or secondary response to hepatocellular enzyme induction. 26,27…”
Section: Resultsmentioning
confidence: 99%